Application of Combination and Relaxation Breath Guided Imagery with Music to Reduce Pain Levels in Patients with Post-Colles Fracture Surgery at the Eri Sadewo Pavilion, Floor V, Gatot Soebroto Army Hospital - Setiawan, Memed Sena; Septia, Bela Amanda (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
Colles fracture is defined as a fracture of the distal radius. Colles fracture is a common trauma to the wrist. This fracture usually occurs most often after falling on a stretched hand or with an outstretched hand. Pain is a problem in post-op Colles Fracture patients. One of the nursing interventions to reduce pain intensity is with deep breathing relaxation techniques and a combination of guided imagery with music. This paper aims to determine the effect of deep breathing relaxation techniques and a combination of guided imagery with music in reducing pain levels in post-fracture surgery patients. This paper uses data collection methods with interviews, observations, physical examinations and documentation studies. Non-Pharmacological interventions were given for 10 minutes in 3 meetings in post-colles fracture surgery patients. The results obtained after being given deep breathing relaxation technique intervention and a combination of guided imagery with music showed a decrease in pain levels from a scale of 5-6 (Moderate) to a scale of 3 (Light). The conclusion is that after conducting a case study, the results showed that there was a change in the pain scale before and after the intervention was given using deep breathing relaxation techniques in combination with guided imagery with music.